A versatile light-switchable nanorod memory : Wurtzite ZnO on perovskite SrTiO3 - Bera, Ashok (2013)
Integrating materials with distinct lattice symmetries and dimensions is an effective design strategy toward realizing novel devices with unprecedented functionalities, but many challenges remain in synthesis and device design. Here, a heterojunction memory made of wurtzite ZnO nanorods grown on perovskite Nb-doped SrTiO3 (NSTO) is reported, the electronic properties of which can be drastically reconfigured by applying a voltage and light. Despite of the distinct lattice structures of ZnO and NSTO, a consistent nature of single crystallinity is achieved in the heterojunctions via the low-temperature solution-based hydrothermal growth. In addition to a high and persistent photoconductivity, the ZnO/NSTO heterojunction diode can be turned into a versatile light-switchable resistive switching memory with highly tunable ON and OFF states. The reversible modification of the effective interfacial energy barrier in the concurrent electronic and ionic processes most likely gives rise to the high susceptibility of the ZnO/NSTO heterojunction to external electric and optical stimuli. Furthermore, this facile synthesis route is promising to be generalized to other novel functional nanodevices integrating materials with diverse structures and properties.